The Europe of elites : a study into the Europeanness of Europe's political and economic elites - Best, Heinrich; Lengyel, György; Verzichelli, Luca (2012)
This is a comprehensive study of how European political and economic leaders think and feel about Europe and about what course future European integration should take.